Violation of the Principle of Cooperation in the Drama Script "Strangers" by Rupert Brook: A Pragmatics Study - Nadila Urningsih; Mochammad Asyhar; Muh. Khairussibyan; Burhanuddin Burhanuddin (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study aims to describe the violation of the principle of cooperation contained in the drama script "Stranger" by Rupert Brook using pragmatic studies. This type of research is qualitative which is descriptive qualitative. The data in this study used the drama script Stranger by Rupert Brook translated by D.Djajakusuma. While the data source is obtained through the internet sourced from achmadnur.blogspot.com which is a translated script from D.Djajakusuma. The method of data collection in this study uses the Simak method with advanced techniques, namely note-taking techniques. Meanwhile, the data analysis method uses two methods, namely Intralingual Pairing as the first step to examine the data through efforts to compare one sentence with other sentences in order to get a dialog that violates the principle of cooperation and Extralingual Pairing to examine something that is outside the language such as concerning the meaning, information and context of speech. The method of presenting the results of data analysis uses Formal methods in the form of parentheses (( )) and Informal methods. The result of this research shows the violation of four maxims of cooperation principle, with the number of them are: 1) violation of quantity maxim 40 utterances; 2) violation of quality maxim 4 utterances; 3) violation of relevance maxim 35 utterances; and 4) violation of manner maxim 2 utterances. The use of dialog that violates the principle of cooperation created by the author aims to create an interesting conflict and also provide tension in a story. This also appears to be related to the theme in the drama script which is a tragedy. So as to create interesting dynamics by deliberately violating the maxim of quantity in order to provide a high effect of tension and curiosity by violating the maxim of relevance.